2019
DOI: 10.31580/jrp.v1i1.517
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Self-confidence with self body image of visually impaired children

Abstract: The purpose of the research work was to know about the relationship between body image satisfaction and self-confidence of visually impaired students. A significant relationship between body image satisfaction and self-confidence was hypothesized. The sample of the study consisted of 100 students with visual impairment, 50 males and 50 females. The study was descriptive in nature with a cross sectional design. The questionnaire consisted of 14 items related to body image satisfaction and 20 items related to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…In addition to developing self-confidence, the participant is also increasingly motivated to do more and very enthusiastic in carrying out the training program provided by the trainer and being increasingly motivated to continue or maintain his achievements. Similar to self-confidence, motivation is also closely related to achievement (Jameel & Shamim, 2019;McMahon et al, 2019). Motivation is the cause of action; without motivation, someone cannot achieve their goals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to developing self-confidence, the participant is also increasingly motivated to do more and very enthusiastic in carrying out the training program provided by the trainer and being increasingly motivated to continue or maintain his achievements. Similar to self-confidence, motivation is also closely related to achievement (Jameel & Shamim, 2019;McMahon et al, 2019). Motivation is the cause of action; without motivation, someone cannot achieve their goals.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoudi and Mohadesi believe that overrated attention to physical beauty in society leaves people prone to fear, doubt, and lack of confidence [ 12 ]. Moreover, some studies have shown that there is a direct relationship between social acceptability, self-confidence, fitness, and body image [ 13 , 23 , 24 ]. The excessive attention of newly emerged media to physical beauty and appearance has fueled fears of being excluded, losing the opportunity of marriage, finding a job, and etc.…”
Section: Discussionmentioning
confidence: 99%
“…Perempuan yang mampu menerima dirinya setelah melahirkan mengindikasikan adanya rasa percaya diri dan rasa syukur dalam dirinya. Individu dengan penerimaan diri yang tinggi cenderung lebih menghargai diri, memiliki kepercayaan diri yang tinggi, dan merasa bersyukur atas kondisi dalam dirinya (Jameel & Shamim, 2019). Perempuan melahirkan yang mampu menghargai diri dan memiliki rasa syukur dalam dirinya akan mengurangi fokus pada penilaian diri sendiri dan orang lain terhadap penampilan diri sendiri, menghargai tubuhnya, dan memiliki pandangan positif terhadap tubuhnya (Homan & Tylka, 2018;Zahra et al, 2022).…”
Section: Pembahasanunclassified